INTEREST IN INDEPENDENT STUDIES PHYSICAL CULTURE OF STUDENTS - Quvvatov Umid Tursunovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article deals with the problem of increasing the level of interest of students of higher educational institutions by organizing independent physical education classes.